Identyfikacja obszarów innowacji proekologicznych w przedsiębiorstwach turystycznych - Przeorek-Smyka, Renata (Identification of Pro-Ecological Innovations Areas in Tourist Enterprises, 2008)
The article presents the basic areas of introducing the changes in tourist enterprises functioning in rural areas. It indicates hypothetical kinds of innovations which can be used in individual areas of economic activities of firms. Moreover, it describes the reasons for introducing pro-ecological innovations, emphasising legal regulation factors.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 67-75